2015
DOI: 10.1039/c4dt02491e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of bimetallic metal–organic framework Cu–Ru-BTC with HKUST-1 structure

Abstract: The bimetallic metal-organic framework Cu-Ru-BTC with the stoichiometric formula Cu2.75Ru0.25(BTC)2·xH2O, which is isoreticular to HKUST-1, was successfully prepared in a direct synthesis using mild reaction conditions. The partial substitution of Cu(2+) by Ru(3+) centers in the paddlewheel structure and the absence of other Ru-containing phases was proven using X-ray absorption spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…This agrees with the HRTEM and FESEM results shown in Figures 1 and 3. Other characteristic peaks for Cu-BTC at 2θ = 15.33 , 18.28 , 20.86 , and 27.86 , corresponding to the d -values 5.7, 4.84, 4.37, and 3.19, respectively, appear in the sample, which agree with the results of Gotthardt et al 43 The XRD of MWCNTs@Cu-BTC is almost same as that of Cu-BTC, as shown in Figure S3.…”
Section: Xrd Analysissupporting
confidence: 88%
“…This agrees with the HRTEM and FESEM results shown in Figures 1 and 3. Other characteristic peaks for Cu-BTC at 2θ = 15.33 , 18.28 , 20.86 , and 27.86 , corresponding to the d -values 5.7, 4.84, 4.37, and 3.19, respectively, appear in the sample, which agree with the results of Gotthardt et al 43 The XRD of MWCNTs@Cu-BTC is almost same as that of Cu-BTC, as shown in Figure S3.…”
Section: Xrd Analysissupporting
confidence: 88%
“…The XRD patterns of Cu‐BTC with and without adding RuCl 3 illustrated in Figure S1a (Supporting Information) exhibit some characteristic peaks of Cu‐BTC disappear and some new diffraction peaks appear after adding RuCl 3 . Hence, we guess that when Ru 3+ ion diffused into the open framework of Cu‐BTC, it triggered an ion‐exchange and partially substituted Cu 2+ center which caused part of framework of Cu‐BTC destroyed . The crystal structure of S‐0 was confirmed by XRD result as illustrated in Figure S1b (Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
“…In order to evaluate the ECSA of both samples, we then employed cyclic voltammetry (CV) measurements to determine the double‐layer capacitance ( C dl ), which is proportional to the ECSA. [21b,27] As shown in Figure S9 (Supporting Information), the C dl of the S‐400‐H catalyst is 42.8 mF cm −2 , which is greater than that of S‐F‐400 (28.9 mF cm −2 ). According the LSV plots, we further obtain the Tafel curves of samples and 20% Pt/C (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Kleist et al. in 2015 reported the synthesis of a bimetallic RuCuBTC which has much lower specific surface area (about 570 m 2 /g) than CuBTC . They proposed increased disorder of the framework due to the higher size difference of Ru(III) and Cu(II) ions (relative to Zn and Cu) might be the reason for the reduced porosity of RuCuBTC.…”
Section: Resultsmentioning
confidence: 99%